Review article: genetic factors that modify the outcome of viral hepatitis. Issue 10 (24th March 2014) - Stättermayer, A. F.; Scherzer, T.; Beinhardt, S.; Rutter, K.; Hofer, H.; Ferenci, P.
Summary Background Genetic factors can play an important role for treatment response and disease progression in chronic viral hepatitis. Aim To review the influence of host genetic factors on the clinical course as well as on treatment response in patients with viral hepatitis. Methods Review of the literature. Results A landmark genome‐wide association study (GWAS) identified polymorphisms in the IL28B gene on chromosome 19 (19q13.13) associated with response to therapy with pegylated interferon‐α (PEG‐IFN) and ribavirin (RBV) and spontaneous viral clearance in acute hepatitis C. Furthermore, IL28B genotype is associated with changes of lipid metabolism and insulin resistance. A further GWAS demonstrated that ITPA genetic variants protect HCV genotype 1 patients from RBV‐induced anaemia. Another polymorphism in the patatin‐like phospholipase domain containing 3 (PNPLA3) is associated with hepatic steatosis. Difficult‐to‐treat hepatitis C patients homozygous for GG had an up to five‐fold lower chance of viral clearance on PEG/RBV than non‐GG patients. In chronic hepatitis B patients treated with PEG‐IFN several retrospective analyses of IL28B rs12980275 and rs12979860 genotypes yielded conflicting results which can be explained by the heterogeneity between the study populations. Some variants of the HLA‐DP locus (HLA‐DPA1 A allele and HLA‐DPB1) protect against progression of chronic hepatitis B infection. Conclusions The determination of IL28B polymorphisms may be useful to individualise treatment options when using PEG/RBV based therapies for chronic hepatitis C infection. In contrast, so far identified genetic factors play only a minor role in chronic hepatitis B infection.